2020
DOI: 10.21203/rs.3.rs-34051/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social Media use and Sexual Behaviour of Undergraduate Students in a Nigerian University

Abstract: While studies have generally explored the implication of social media on education, crime, and communication, there is a paucity of studies exploring the influence of social media on sexual behaviour. Thus, this study aims to investigate the role of social media on sexual behaviour among 195 undergraduate students in the Niger Delta University, Bayelsa, Nigeria. This cross-sectional study was anchored on the uses and gratification theory (UGT). Data for this study were generated through the use of a structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…A study conducted by [16] on social media use identified that adolescent changes are influenced by the ease of access to information via social media channels such as the internet, mobile phones, and computer and satellite televisions. Also, in consonance with this study was that conducted by [18] which showed that social media influences the risky sexual behaviour via the use of WhatsApp, Instagram to mention a few, and that conducted by [19] which reported that social media shaped the sexual health attitudes and behaviours of young undergraduates. Also, in line with this study finding was that carried out by [17] on the influence of social media use on risky sexual behaviours of undergraduate Students in Ilorin, which showed that there is significant association between exposure to sexual contents in social media and risky sexual behaviour among undergraduate students.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A study conducted by [16] on social media use identified that adolescent changes are influenced by the ease of access to information via social media channels such as the internet, mobile phones, and computer and satellite televisions. Also, in consonance with this study was that conducted by [18] which showed that social media influences the risky sexual behaviour via the use of WhatsApp, Instagram to mention a few, and that conducted by [19] which reported that social media shaped the sexual health attitudes and behaviours of young undergraduates. Also, in line with this study finding was that carried out by [17] on the influence of social media use on risky sexual behaviours of undergraduate Students in Ilorin, which showed that there is significant association between exposure to sexual contents in social media and risky sexual behaviour among undergraduate students.…”
Section: Discussionsupporting
confidence: 79%
“…Study on the influence of social media use on sexual behaviour of undergraduate students in Ilorin showed that there is significant association between exposure to sexual contents in social media and risky sexual behaviours among undergraduate students [17]. A study showed that social media influences the risky sexual behaviour via the use of WhatsApp, Instagram to mention a few [18]. Also [19] reported that social media shape the sexual health attitudes and behaviours of young undergraduates, which showed that out of 226 respondents who had ever had sex, 226 (100%), 37 (16.4%), 31 (13.7%), and 10 (4.4%) practiced coitus, oral sex, masturbation, and anal sex, respectively; 33 (14.6%) had had sex with commercial sex workers.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents who had sexual contact might relatively have high level of risk perception like being vulnerable for sexual transmitted diseases and for unwanted pregnancy. Therefore, they are more intended to use sexual and reproductive service such as family planning, HIV test, and pregnancy service (25)(26)(27). In the current pooled meta-analysis, having pocket money had statistically signi cant association with SRH service utilization.…”
Section: Discussionmentioning
confidence: 99%